Handling Fruit and Vegetable Waste by Breeding BSF Larvae at the Penebel Village Waste Management Center, Tabanan - Mardewi, Ni Ketut; Suryati, Luh; Kartini, Luh (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2022)
The KSM Penebel Berlian Waste Management Center is a non-governmental group with the aim of managing waste from households and from the traditional market of Penebel Village, which is in the form of organic waste and inorganic waste. In a day about 10 cubic feet of waste enters the KSM Penebel Berlian, 60% of which is organic waste. So far, organic waste is processed into compost, but it takes a long time while the waste is sent every day so that there is more and more organic waste and has not had time to be processed. It was also tried to process organic waste into eco-enzymes but failed because the community did not understand how it was made and the process of hardening the eco-enzym until it matured took a minimum of three months. The group wants to cultivate maggots intensively in KSM because the raw materials for maggot feed are adequate, can handle the problem of organic waste faster, odorless and involve group members. Maggot cultivation results will be used as poultry feed and fish feed, aquaculture waste will be used as organic fertilizer. Maggots are very positive to be developed into an alternative solution to the problem of organic waste without causing odors. Maggot larva of the BSF Fly (Black Shoulder Fly) which has the Latin name Hermetia illucens or black soldier fly is a large black fly and is not pathogenic. This cycle takes 40 to 45 days only. Community service activities have been running smoothly. Members of KSM Penebel Berlian have been able to independently produce BSF maggots from vegetable and fruit waste. Thus, the problem of organic waste in Penebel Village is also resolved, does not cause odors, waste does not accumulate, is handled in a shorter time with the concept of zero waste, and produces a product, namely BSF maggots that can be used as fish and poultry feed.